المقاولاتية وأثرها على النمو الاقتصادي في تركيا: خلال 2009-2016 - عبد الرزاق بن علي (My University, 2018)
تهدف هذه الدراسة لعرض نشاط المقاولاتية وبرامج الدعم التي تقدمها الحكومات التركية للمؤسسات الصغيرة والمتوسطة، وأثر ذلك النشاط على النمو الاقتصادي بها. بهدف استكشاف قوة المؤسسات الصغيرة والمتوسطة في الاقتصاد التركي الناشئ والمتنامي. وقد اعتمدت الدراسة لاختبار فرضيتها، على المنهج الوصفي التحليلي. وكشفت الدراسة ، أن تركيا لها بدايات مبكرة في المقاولاتية وبرامج حفزها ودعمها، وقد تم تفعيلها أكثر منذ عام 2012؛ وذلك، كان له أثر في ارتفاع أعداد المؤسسات الصغيرة والمتوسطة وحجم العمالة بها، إضافة إلى تحقيق قيمة إضافية ايجابية، خلال فترة الدراسة 2006-2016؛ وعليه فإن فرضية الدراسة صحيحة. رغم أن الأثر ليس كبيرا، فقد يرجع إلى مناخ وتحديات الوضع السياسي المحلي والدولي لتركيا، وذي العلاقة بمنتجات وأسواق المؤسسات الصغيرة والمتوسطة التركية. The aim of this study is to present the entrepreneurial activity and support programs offered by the Turkish governments to small and medium enterprises, and the impact of this activity on economic growth. With a view to exploring the strength of SMEs in Turkey's emerging and growing economy.. To test the hypothesis of the study; was to rely on descriptive analytical approach. The study showed that Turkey has early beginnings in entrepreneurship, and programs to its stimulate and support, Has been more activated since 2012. This has had an impact on the increase in the number of SMEs and the size of their employment, in addition to achieving positive additional value, during 2009-2016. Therefore, the hypothesis of the study is correct. Although the impact is not significant, it may be due to the climate and challenges of the domestic and international political situation of Turkey, which is related to the products and markets of Turkish SMEs
Keywords: مؤسسات صغيرة ومتوسطة، ، نمو اقتصادي ، مقاولاتية ، تركيا JEL : P42, O4, M13